Prevalence of Smartphone Addiction and its Association with Impulsivity among Undergraduate Medical Students - Kulsoom Lashari, Sangeet, Muhammad Ilyas, Raz Muhammad Bazai, Kartaar Saahil, Rida Jawaid, Muhammad Bilal Kaleem (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: With the increasing ubiquity of smartphones and their integral role in modern life, understanding the factors contributing to smartphone addiction, especially in high-pressure academic environments, is crucial. Objective: This study investigates the prevalence and determinants of smartphone addiction among undergraduate medical students in Pakistan. With This research specifically explores the relationship between impulsivity, stress levels, social pressures, and smartphone addiction. Methodology: A structured questionnaire survey, comprising validated scales for each construct, was administered to a sample of undergraduate medical students across various years of study. The study employs a cross-sectional design and uses stratified random sampling for data collection. Results and Findings: The results indicate a significant positive association between impulsivity and smartphone addiction. Furthermore, stress levels and social pressures were also found to be positively correlated with smartphone addiction, suggesting a multifaceted nature of this issue. These findings contribute to the growing body of literature on digital addiction and offer practical insights for educational institutions and policymakers. The study highlights the need for holistic intervention strategies addressing both personal traits and environmental factors to mitigate smartphone addiction. The limitations of the study and recommendations for future research are also discussed. Keywords: Smartphone Addiction, Impulsivity, Stress Levels, Social Pressures, Undergraduate Medical Students, Digital Addiction, Pakistan